Serum and Synovial Fluid Levels of Interleukin-17A in Primary Knee Osteoarthritis Patients: Correlations With Functional Status, Pain, and Disease Severity - Shereen KAMEL,; Rehab KHALAF,; Hend MONESS,; Shimaa AHMED, (Archives of Rheumatology, 2022)
Objectives: This study aims to assess the serum and synovial fluid (SF) levels of interleukin (IL)-17A in primary knee osteoarthritis (KOA) patients and to study their correlations with functional status, pain, and disease severity. Patients and methods: This cross-sectional study was conducted between December 2017 and March 2018 and it included 70 patients (46 males, 24 females; mean age 57.3±10.0 years; range 34 to 76 years) with primary KOA and 30 age-, sex-, and body mass index-matched healthy individuals (20 males, 10 females; mean age 53.3±10.3 years; range, 35 to 70 years). Western Ontario and McMaster Universities osteoarthritis index (WOMAC), visual analog scale (VAS), Lequesne index, and Kellgren and Lawrence (KL) grading scale were used for assessment of the disease. IL-17A levels were measured in the serum for patients and healthy controls, and in SF for patients only using an enzyme-linked immunosorbent assay. Results: Serum levels of IL-17A were significantly higher in KOA patients than controls (p=0.04). A positive correlation was found between serum and SF IL-17A levels. Serum and SF IL-17A levels had positive correlations with VAS, WOMAC pain score, Lequesne pain score, WOMAC function score, and Lequesne index. SF IL-17A levels had strong positive correlations with radiographic severity (KL grade) and duration of OA. Conclusion: Higher IL-17A levels in primary KOA patients were significantly associated with longer disease duration, higher pain scores, worse quality of life, extreme disability, and advanced structural damage. Therapeutics that target IL-17A warrant further investigation.